2020
DOI: 10.1186/s12970-020-00368-3
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramide supplementation reduces eccentric exercise-induced inflammation in young men and women

Abstract: Background Avenanthramides (AVA) are a group of di-phenolic acids found only in oats and have shown antioxidant and anti-inflammatory effects in vitro and in vivo. Eccentric muscle contraction is intimately involved in rigorous exercise that activates systemic and local inflammatory responses. The objective of the study is to evaluate whether chronic AVA supplementation could attenuate peripheral inflammatory and immunological markers in human subjects in response to an acute bout of downhill runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…Avenanthramides are polyphenolics unique to oats and display anti-inflammatory effects. Using an acute eccentric exercise-induced inflammation model, avenanthramide supplementation (20.6 mg/day for 8 weeks) reduced circulatory inflammatory cytokines and inhibited expression of chemokines and cell adhesion molecules in 24 young adults [ 110 ]. Similarly, avenanthramides (9.2 mg/d for 8 weeks) blunted acute eccentric exercise-induced neutrophil respiratory burst in 16 young women.…”
Section: Polyphenolicsmentioning
confidence: 99%
“…Avenanthramides are polyphenolics unique to oats and display anti-inflammatory effects. Using an acute eccentric exercise-induced inflammation model, avenanthramide supplementation (20.6 mg/day for 8 weeks) reduced circulatory inflammatory cytokines and inhibited expression of chemokines and cell adhesion molecules in 24 young adults [ 110 ]. Similarly, avenanthramides (9.2 mg/d for 8 weeks) blunted acute eccentric exercise-induced neutrophil respiratory burst in 16 young women.…”
Section: Polyphenolicsmentioning
confidence: 99%
“…The majority of currently available studies addressed the effects of phenol-rich foods on exercise-induced oxidative stress, including dark chocolate [ 29 , 30 , 31 ], high-flavanol cocoa drink [ 32 ], green tea [ 33 ], mate tea [ 34 ], New Zealand blueberry smoothie [ 35 ], blueberries [ 36 , 37 ], grape juice [ 38 , 39 ], Montmorency cherry juice [ 40 ], tart cherry juice [ 41 ], oatmeal [ 42 ], avenanthramides (AVA)-rich cookie [ 43 , 44 ], juçara juice [ 45 ], Sanguinello cultivar red orange juice [ 46 ], and purple sweet potato leaves [ 47 ]. Frequently, the effects of dietary strategies on exercise-induced stress are evaluated within short-term [ 29 , 32 , 35 , 36 , 38 , 42 , 45 ], as well as long-term interventions [ 30 , 31 , 33 , 34 , 37 , 39 , 40 , 41 , 43 , 44 , 46 , 47 ]. Across all studies, there is a compelling amount of evidence suggesting that different dietary regimens are viable tools for decreasing exercise-induced oxidative stress.…”
Section: Dietary Strategiesmentioning
confidence: 99%
“…In this review, diets with antioxidant effects have demonstrated to reduce inflammatory markers including neutrophil respiratory burst (NRB), interleukin-6 (IL-6), nuclear factor-kappa B (NF-κB), granulocyte-colony stimulating factor (G-CSF), interleukin-1 receptor antagonist (IL-1Ra), soluble vascular cell adhesion molecule-1 (sVCAM-1). In this narrative review, n = 3 studies ([ 43 , 44 , 54 ]) showed decreases in inflammatory markers from the diet interventions.…”
Section: Effects On Biomarkers Of Exercise-induced Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations